STORYTELLING DALAM KAMPANYE PELESTARIAN LINGKUNGAN - Stepanus Bo'do; Fadhliah; Sitti Murni Kaddi; Kudratullah; Nurliana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
This research aims to find out and understand the Story Telling training program in the Environmental Conservation Campaign implemented by the Tana Sanggamu Foundation in Toaya Village. This training aims to increase media management capacity for environmental advocacy by the community in Toaya Village, Sindue District, Donggala Regency, Central Sulawesi. Efforts to develop community capacity are expected to be a sustainable process to increase community awareness, especially youth, of the importance of preserving the environment. This research uses a descriptive qualitative approach and is carried out in the form of Participatory Action Research. The results of this research show that the Tana Sanggamu Foundation is conducting story telling training as an environmental conservation campaign technique by utilizing village youth's interest in social media, films and games as learning and training media. Delivery of material using these three training media applies persuasive techniques including dissonance, integration, association, giving rewards, generating fear, obedience and red-herring.